1,2,3,4,6-Pentagalloyl Glucose, a RBD-ACE2 Binding Inhibitor to Prevent SARS-CoV-2 Infection - Chen, Rui Hong; Yang, Li Jun; Hamdoun, Sami; Chung, Sookja Kim; Lam, Christopher Wai-kei; Zhang, Kai Xi; Guo, Xiaoling; Xia, Chenglai; Law, Betty Yuen Kwan; Wong, Vincent Kam Wai (Frontiers in Pharmacology, 2021)
The outbreak of SARS-CoV-2 virus caused more than 80,155,187 confirmed COVID-19 cases worldwide, which has posed a serious threat to global public health and the economy. The development of vaccines and discovery of novel drugs for COVID-19 are urgently needed. Although the FDA-approved SARS-CoV-2 vaccines has been launched in many countries recently, the strength of safety, stringent storage condition and the possibly short-term immunized efficacy remain as the major challenges in the popularity and recognition of using vaccines against SARS-CoV-2. With the spike-receptor binding domain (RBD) of SARS-CoV-2 being responsible for binding to human angiotensin-converting enzyme 2 receptor (hACE2), ACE2 is identified as the receptor for the entry and viral infection of SARS-CoV-2. In this study, molecular docking and biolayer interferometry (BLI) binding assay were adopted to determine the direct molecular interactions between natural small-molecule, 1,2,3,4,6-Pentagalloyl glucose (PGG) and the spike-RBD of the SARS-CoV-2. Our results showed that PGG preferentially binds to a pocket that contains residues Glu 340 to Lys 356 of spike-RBD with a relatively low binding energy of -8 kcal/mol. BLI assay further confirmed that PGG exhibits a relatively strong binding affinity to SARS-CoV-2-RBD protein in comparison to hACE2. In addition, both ELISA and immunocytochemistry assay proved that PGG blocks SARS-CoV-2-RBD binding to hACE2 dose dependently in cellular level. Notably, PGG was confirmed to abolish the infectious property of RBD-pseudotyped lentivirus in hACE2 overexpressing HEK293 cells, which mimicked the entry of wild type SARS-CoV-2 virus in human host cells. Finally, maximal tolerated dose (MTD) studies revealed that up to 200 mg/kg/day of PGG was confirmed orally safe in mice. Our findings suggest that PGG may be a safe and potential antiviral agent against the COVID-19 by blockade the fusion of SARS-CoV-2 spike-RBD to hACE2 receptors. Therefore, PGG may be considered as a safe and natural antiviral agent for its possible preventive application in daily anti-virus hygienic products such as a disinfectant spray or face mask.